Laparoscopic colectomy after transcatheter aortic valve implantation in an elderly patient with obstructive descending colon cancer and severe aortic stenosis: a case report - Koki Tamai; Shu Okamura; Tomohiro Kitahara; Takayuki Minoji; Hiroyuki Takabatake; Noriyuki Watanabe; Noriyuki Yamamura; Nariaki Fukuchi; Chikara Ebisui; Hideoki Yokouchi; Masaki Tsuda; Isamu Mizote; et al. (Surgical Case Reports)
Abstract Background The demand for laparoscopic colectomy is increasing due to greater number of elderly colon cancer patients, and it is important to evaluate existing comorbidities to ensure perioperative safety. Aortic stenosis (AS) is one of the most common heart diseases in the elderly, and elderly cancer patients with severe AS may be considered ineligible for optimal cancer treatment if they cannot endure surgical aortic valve replacement (SAVR). Recently, transcatheter aortic valve implantation (TAVI) has become a valid option in patients who are high risk for SAVR. We herein present the first case of an elderly cancer patient with severe AS who underwent laparoscopic colectomy after TAVI. Case presentation An 87-year-old woman with a history of multiple cardiovascular diseases was diagnosed with obstructive descending colon cancer and initially underwent colonic stenting. However, as preoperative echocardiography revealed severe AS, she underwent TAVI prior to the colectomy to reduce perioperative risk. TAVI was chosen instead of SAVR due to high SAVR mortality risk, and laparoscopic colectomy was performed 22 days after TAVI. Her postoperative course was uneventful, and she was discharged 14 days later without any deterioration in general condition. No recurrence was observed at more than 1 year, even without adjuvant therapy. Conclusion TAVI facilitated subsequent laparoscopic colectomy in an elderly cancer patient with severe AS. Our case report shows that TAVI may enable further cancer treatment even in patients with severe AS, who may otherwise be considered not suitable for such treatments.